Islam without Europe: Traditions of Reform in Eighteenth-Century Islamic Thought By Ahmad S. Dallal (Chapel Hill, NC: The University of North Carolina Press, 2018. 436 pages.) (American Journal of Islam and Society, 2019)
It is hard to exaggerate the scope or scale of this major monograph from one of the foremost Arab Muslim scholars of his generation, Ahmad Dallal, formerly Provost at the American University of Beirut, and now Dean of Georgetown University Qatar.In carefully orchestrated arguments, with massive documentary evidence, Dallal addresses eighteenth century theological/juridical issues across the span of the Muslim world. He touches on intellectual giants and reform movements from Senegal to Syria, from Yemen to India, delving deeply into complex debates that continue to resonate. Islam without Europe catapults Dallal into the company of revisionists who are also global historians, those looking for a way to redefine Islam outside the parameters of European historical conventions.To download full review, click on PDF.